Philosophy Studies in Elementary Schools - Helda Kusuma Wardani (Journal of Elementary School Education, 2024)
When a teacher thinks about why an educational act is done? The answer to that question will boil down to the beginning of the process of the education system. The beginning and estuary of the process of the education system are deep-rooted ideas about education itself which are often referred to as educational philosophy. The need for the study of educational philosophy is urgent to help every Elementary School ( ES ) teacher realize the importance of answering the question "why do educational acts or learning acts do?" Departing from this background, literature study research was carried out which aimed to explain and criticize (1) the philosophical foundations in ES , (2) the role of philosophical foundations in ES, (3) the implementation of philosophy in ES, and (4) ) philosophical problems in ES. A literature study of the philosophy of education in elementary schools found (1) There are 5 (five) educational philosophies implemented in elementary education explicitly or implicitly, namely the educational philosophy of Pancasilaism, progressivism, perennialism, essentialism, and reconstructionism. (2) The role of the foundation of educational philosophy includes the role as a source of formulation of institutional educational objectives or Graduate Competency Standards, a practical role as a source of planning, implementing, and assessing education, and acting as a policy foundation at the macro, messo, and micro levels. (3) The implementation of educational philosophy in education in elementary schools includes planning, implementing, and assessing education. (4) Problems of educational philosophy in ES , including (a) uniformity vs. diversity, (b) the practice of identity politics, (c) teacher comfort zones, (d) dynamics of demands for change, and (e) incremental innovation.